Pengaruh Latihan Split Kiri, Split Kanan dan Split Tengah terhadap Peningkatan Kelentukan (Flexibility) Atlet Pemula Senam Ritmik Banjarbaru - Ahmat Fauzi; Bonita Amalia; Tri Ari Fitrianto (Ilmu Olahraga, 2022)
The purpose of this study was to determine the effect of left split, right split, and center split training on increasing flexibility for beginner athletes in Banjarbaru Rhythmic Gymnastics. The method used in this research is a quasi-experimental method. The purpose of a quasi-experiment is to obtain information that is an approximation to the information that can be obtained with the actual experiment under conditions where it is not possible to control and manipulate all relevant variables. The results of this study (1) there is a significant effect between the left split, right split, and center split to increase flexibility (flexibility) of beginner athletes in Banjarbaru Rhythmic Gymnastics. From the calculations that have been carried out for the left split training group, a t value of 4.5 was obtained, the right split exercise group obtained a t value of 1.360, and the middle split exercise group obtained a t value of 27.8, it was greater than 5%, namely 4.303. (2) Right split exercise has a better effect on increasing flexibility for beginner athletes in Banjarbaru Rhythmic Gymnastics.